Capacity of MC-FDMA in mobile communications - Nogueroles, R.; Bossert, M.; Zyablov, V. (Waves of the year 2000+ : PIMRC'97 : the 8th IEEE International Symposium on Personal, Indoor, and Mobile Radio Communications : September 1-4, 1997 : the technical program, proceedings, 1997)
We study the performance of MC-FDMA when applied in mobile communications. We describe two MC-FDMA strategies with control from the base station, telling the users which channels to use. Then we describe a strategy without control from the base station, where the users randomly select their subchannels. For this strategy we describe a joint-detection decoding algorithm with interference cancellation which increases the performance. We compute the optimum number of selected subchannels per user for the random strategy, and describe an adaptive optimum random strategy. In order to compare the different strategies we compute the user capacity, that is the amount of information per transmitted block. Since the number of users in cities is bigger, we consider typical urban channels (TUX) for our simulations.